Clinical Pharmacogenetics Implementation Consortium Guideline for HLA Genotype and Use of Carbamazepine and Oxcarbazepine: 2017 Update. Issue 4 (2nd February 2018) - Phillips, Elizabeth J.; Sukasem, Chonlaphat; Whirl‐Carrillo, Michelle; Müller, Daniel J.; Dunnenberger, Henry M.; Chantratita, Wasun; Goldspiel, Barry; Chen, Yuan‐Tsong; Carleton, Bruce C.; George, Alfred L.; Mushiroda, Taisei; Klein, Teri; et al.
Abstract : The variant allele HLA‐B*15:02 is strongly associated with greater risk of Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) in patients treated with carbamazepine or oxcarbazepine. The variant allele HLA‐A*31:01 is associated with greater risk of maculopapular exanthema, drug reaction with eosinophilia and systemic symptoms, and SJS/TEN in patients treated with carbamazepine. We summarize evidence from the published literature supporting these associations and provide recommendations for carbamazepine and oxcarbazepine use based on HLA genotypes.